Potencial de heterotrofia do reservatório de Barra Bonita (SP), com ênfase na decomposição de polissacarídeos extracelulares de espécies fitoplânctônicas - Antonio, Rogério Marchetto (2004)
The extracellular polysaccharides (EPS) excreted by algae comprise an important fraction of organic matter produced by the phytoplankton in fresh and salt waters. Thus EPS can be considered an important organic carbon source for microorganisms, besides their possible contribution for humic compounds formation. In this context, this study aimed to describe the seasonal variation of dissolved organic matter (DOM) heterotrophy in function of limnological variables of the Barra Bonita reservoir (Brazil, SP) and to quantify the transfers of dissolved organic carbon (DOC) from the EPS to microorganisms, mineralization and humic substances formation. It was verified the rise of mineralization potentials (aerobic and anaerobic) during spring (September to November) and summer (from December to February). It was also verified that in drier and colder months (July and August) the mineralization processes involved more oxygen consumption per carbon mineralized, that is to say, occurred a rise of O/C stoichiometry values. Statistical analyses between heterotrophy potentials and limnological variables revealed that heterotrophy potentials (aerobic and anaerobic) were basically linked to DOC contents in the water. A kinetic model was developed aiming to describe the decomposition of EPS from different algae species and it allowed us to establish a general tendency for the fates of EPS when they are submitted to decomposition in reservoir water. The results showed that about 4.0 % of the DOC from the EPS was transferred to humic substances; 23.0 % was mineralized after formation of microorganisms (by their decomposition) and approximately 73.5 % was mineralized by catabolic processes.